إنعكاس توازن السلطة التنفيذية على استقرار النظام السياسي الجزائري - مسعودي تمام (Universty Of El-oued جامعة الوادي, 2025)
الملخص: إن النظام السياسي في الجزائر عرف العديد من الأزمات ، ومن خلال دراستنا هاته حاولنا الوقوف على الأحكام الدستورية المتعلقة بالسلطة التنفيذية، وما مدى تأثيرها على إستقرار النظام السياسي، إما بالسلب أو بالإيجاب، ولقد كانت دراستنا هاته محددة من خلال فترتين، الأولى درسنا فيها ما مدى إستقرار النظام السياسي بالرجوع إلى أحكام الدساتير التي كانت ما قبل التعديل الدستوري لسنة 2020، والثانية تعتبر تقدير إذا كان التعديل الدستوري لسنة 2020 سيصنع الاستقرار المفقود، والذي وقفنا عليه هو أن الأحكام الدستورية المتعلقة بالسلطة التنفيذية لم تخلق توازنا في الدساتير التي سبقت 2020، وهو ما أثر سلبا على إستقرار النظام السياسي، وخلق حالات عدم إستقرار حادة، فالتوازن الداخلي بين رئيس الجمهورية والقطب الثاني مهما كانت تسميته كان مفقود، وهو نفس الوضع فيما يخص التوازن الخارجي بين السلطة التنفيذية والسلطة التشريعية من جهة، وبينها وبين السلطة القضائية من جهة أخرى، ومن خلال هذا خلصنا إلى أن الإختلالات في توازن السلطة التنفيذية كان لها الأثر السلبي على إستقرار النظام السياسي الجزائري ما قبل التعديل الدستوري لسنة 2020، وكانت جميع التعديلات الدستورية تهدف إلى ضمان إستمرارية النظام وليست من أجل إستقراه، والفرق كبير بين هذا وذاك. أما فيما يخص تقدير مدى توفيق المؤسس الدستوري في صياغة أحكام جديدة من خلال التعديل الأخير، فخلصنا إلى أن هناك توجه نحو خلق نوع من التوازن الداخلي والخارجي للسلطة التنفيذية لكن هو غيـر كاف، ونضيف إلى ذلك عدم الإستفادة من التجارب الدستورية السابقة بما يكفل الاستقرار التام. Abstract: The political system in Algeria has experienced numerous crises. In this study, we aimed to examine the constitutional provisions related to the executive authority and assess their impact on the stability of the political system, whether positively or negatively. Our study was divided into two periods: the first examined the stability of the political system by reviewing constitutional provisions before the 2020 constitutional amendment, while the second focused on evaluating whether the 2020 amendment could bring about the needed stability. Our findings indicate that the constitutional provisions concerning the executive authority did not create a balance in the pre-2020 constitutions, which negatively affected the political system's stability, resulting in acute instability. The internal balance between the president and the counterpart authority, regardless of its designation, was lacking. The same applies to the external balance between the executive and legislative powers on one side, and the executive and judiciary on the other. Thus, we concluded that the imbalance in executive authority had a negative impact on the stability of Algeria's political system prior to the 2020 amendment. All previous constitutional amendments aimed at ensuring the continuity of the system rather than its stabilitythere is a significant difference between the two. As for assessing the success of the constitutional drafters in formulating new provisions through the recent amendment, we concluded that while there is a tendency to create some internal and external balance for the executive authority, it remains insufficient. Additionally, past constitutional experiences were not sufficiently leveraged to ensure complete stability.
أطروحة دكتوراه
Keywords: السلطة; الاستقرار; التعايش السياسي; الفصل; التوازن; Authority; Stability; Political Coexistence; Separation; Balance